2022
DOI: 10.5194/amt-15-2993-2022
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of holographic imaging and single-particle forward light scattering in situ measurements of liquid clouds in changing atmospheric conditions

Abstract: Abstract. Upon a new measurement technique, it is possible to sharpen the determination of microphysical properties of cloud droplets using high resolving power imaging. The shape, size, and position of each particle inside a well-defined, three-dimensional sample volume can be measured with holographic methods without assumptions of particle properties. In situ cloud measurements were carried out at the Puijo station in Kuopio, Finland, focusing on intercomparisons between cloud droplet analyzers over 2 month… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Wind direction and wind speed also cause different droplets loss efficiency. Tiitta et al [35] found that the bigger the angular deviation from the coaxial structure, the greater the droplets loss. The average wind speed on the mountain station is 10 m/s, and the wind direction is variable.…”
Section: The Analysis Of Reasons Causing the Differencementioning
confidence: 99%
See 1 more Smart Citation
“…Wind direction and wind speed also cause different droplets loss efficiency. Tiitta et al [35] found that the bigger the angular deviation from the coaxial structure, the greater the droplets loss. The average wind speed on the mountain station is 10 m/s, and the wind direction is variable.…”
Section: The Analysis Of Reasons Causing the Differencementioning
confidence: 99%
“…Methods for in situ measurement include light scattering and holographic imaging. The measurement methods based on light scattering exploit the intensity of forward scattered light from individual droplets to determine the size of droplets [35]. Instruments based on the method are, for example, the fog monitor 100 (FM100) and the fog monitor 120 (FM120).…”
Section: Introductionmentioning
confidence: 99%